Correlates of High-Risk and Low-Risk Alcohol Use among College Students in Kerala, India. Issue 1 (1st January 2018) - Jaisoorya, T. S.; Gowda, Guru S.; Nair, B. Sivasankaran; Menon, Priya G.; Rani, Anjana; Radhakrishnan, K. S.; Revamma, M.; Jeevan, C. R.; Kishore, Anupam; Thennarasu, K.; Benegal, Vivek
ABSTRACT: This study describes the prevalence and correlates of alcohol use among college students in Ernakulam, Kerala State, India. A total of 5784 students from 58 colleges selected by stratified random sampling completed a questionnaire incorporating standardized instruments. The prevalence of lifetime alcohol use was 21.4% with a male predominance. Among users, low-risk, hazardous, and dependent use were 80.2%, 18.3% and 0.9% respectively. Initiation was mostly with friends (45.3%). Both low-risk and high-risk alcohol users (hazardous and dependent users), in comparison to abstainers, had higher odds of being older, non-Muslim, having a part-time job, using other substances, and exposure to sexual abuse. Students who reported low-risk use also had an urban background, more severe psychological distress and suicidal thoughts, while high-risk users had attention deficit hyperactivity disorder (ADHD) symptoms. Students who reported high-risk use compared to low-risk users had higher odds of having a part-time job, tobacco use, and ADHD symptoms. Alcohol use among college students is common, with both low- and high-risk drinking associated with significant morbidity. This study highlights the need to promote public health policies to target and prevent all patterns of alcohol use among young people.